Paciente femenino de 71 años de edad con insuficiencia respiratoria aguda. - Gaibor Vega, Gisella Tatiana (2021)
As part of the health staff, I want to contribute to the positioning of the severity of acute respiratory failure in elderly patients, which is a factor that affects the high incidence of acute respiratory infections in this population. Acute respiratory failure is one of the reasons for consultation in different hospitals that is why you must make known everything that comes with suffering from this disease. The symptoms suffered by the patient should be evaluated in addition to carrying out the respective complementary tests. Laboratory tests such as chest X-rays and blood gases are the main diagnostic methods to verify or rule out other types of lung involvement. After analyzing the results of the examination and the required radiographs, based on the blood and radiology results, it is determined that the values are higher than normal, so the doctor orders the admission of the patient to the hospital to provide better routine services. Among the elderly, it is one of the leading causes of universally infectious death in the world, because the mortality rate from the disease doubles with age and has a high incidence. That is why this work was carried out focused on a 71-year-old female patient which compiles everything related to acute respiratory failure, likewise will help the different professionals in the health area to know one more this disease and in turn how treatment should be applied in patients with acute respiratory failure.